Comparative analysis of four nuclei in the human brainstem: Individual differences, left-right asymmetry, species differences - Joan S. Baizer; Sandra F. Witelson (Frontiers Media S.A., 2023)
IntroductionIt is commonly thought that while the organization of the cerebral cortex changes dramatically over evolution, the organization of the brainstem is conserved across species. It is further assumed that, as in other species, brainstem organization is similar from one human to the next. We will review our data on four human brainstem nuclei that suggest that both ideas may need modification.MethodsWe have studied the neuroanatomical and neurochemical organization of the nucleus paramedianus dorsalis (PMD), the principal nucleus of the inferior olive (IOpr), the arcuate nucleus of the medulla (Arc) and the dorsal cochlear nucleus (DC). We compared these human brainstem nuclei to nuclei in other mammals including chimpanzees, monkeys, cats and rodents. We studied human cases from the Witelson Normal Brain collection using Nissl and immunostained sections, and examined archival Nissl and immunostained sections from other species.ResultsWe found significant individual variability in the size and shape of brainstem structures among humans. There is left-right asymmetry in the size and appearance of nuclei, dramatically so in the IOpr and Arc. In humans there are nuclei, e.g., the PMD and the Arc, not seen in several other species. In addition, there are brainstem structures that are conserved across species but show major expansion in humans, e.g., the IOpr. Finally, there are nuclei, e.g. the DC, that show major differences in structure among species.DiscussionOverall, the results suggest several principles of human brainstem organization that distinguish humans from other species. Studying the functional correlates of, and the genetic contributions to, these brainstem characteristics are important future research directions.